Still a perfect model? : The gender impact of vocational training in Germany - Haasler, Simone R. [Verfasser]; Gottschall, Karin [Verfasser] (My University, 2015)
"Reconstructing the parallel structure of 'dual' and 'school-based' vocational routes reveals the close connection between the German vocational training system and the segmentation of the labour market by gender. The example of jobs in childcare and pre-primary education shows that the legacy of semi-professionalism in these occupations is not just rooted in the nature of training and working conditions, but complexly interlinks with the prevalence of the male breadwinner model sustained by social policy regulations and the German taxation system. In France, by contrast, the central state takes responsibility for the provision of childcare from zero to six years of age to support female labour force participation and dual-earner couples. This has also fostered professionalisation in the respective occupations. Whilst this may not necessarily induce a degendering process at the level of horizontal segregation of vocational qualifications, it facilitates gender equality in terms of vertical mobility and the professional status of women." (Author's abstract; BIBB-Doku)
Keywords: S 1.3.3 Vollzeitschulische Berufsausbildung; S 6.4.5.4 Sozialpflegerische Berufe; G 1.2 Arbeitsmarkt; G 2.4.5 Gender Mainstreaming; I 2.1 Deutschland; I 2.2.1 Westeuropa; Schulische Berufsausbildung; Vollzeitschule; Erzieherberuf; Arbeitsmarktsegmentation; Geschlechterrolle; Bundesrepublik Deutschland; Frankreich